Ring oscillator physically unclonable function using sequential ring oscillator pairs for more challenge-response-pairs - Julius Han Loong Teo; Noor Alia Nor Hashim; Azrul Ghazali; Fazrena Azlee Hamid (Institute of Advanced Engineering and Science, 2019)
The ring oscillator physically unclonable function (ROPUF) is one of the several types of PUF that has great potential to be used for security purposes. An alternative ROPUF design is proposed with two major differences. Firstly, the memristor is included in the ring oscillators as it is claimed to produce a more random oscillation frequency. Other reasons are its memory-like properties and variable memristance, relative compatibility with CMOS, and small size. Secondly, a different method of generating the response is implemented whereby a sequence of selection of ring oscillator pairs are used to generate a multiple bit response, rather than using only one ring oscillator pair to generate a single bit response. This method significantly expands the set of challenge-response pairs. The proposed memristor-based ROPUF shows 48.57%, 51.43%, and 51.43% for uniqueness, uniformity, and bit-aliasing, respectively. Also, modelling by support vector machine (SVM) on the proposed memristor-based ROPUF only shows 61.95% accuracy, thereby indicating strong resistance against SVM.